Dinamika Verbal Abuse Pada Siswa di Era BANI: Perspektif Gender dan Jenjang Pendidikan - Muh Syawal Hikmah; Henny Indreswari; Khairul Bariyyah; IM Hambali; Adi Atmoko (Program Studi Bimbingan dan Konseling, 2026)
his study aims to analyze the dynamics of verbal abuse among students in the BANI (Brittle, Anxious, Nonlinear, Incomprehensible) era based on gender and educational level. The novelty of this study lies in the integration of BANI era concepts in the study of verbal abuse using descriptive quantitative methods. The results show that verbal abuse tends to be in the moderate category (85.84%), with the most dominant forms being verbal aggression (M=7.774), insults/name-calling (M=3.619), blaming (M=2.482), and self-deprecation (M=2.181), while forms involving threats (M=1.071), and negative criticism (M=1.084) appear relatively lower. Male students tend to show higher levels of verbal abuse than female students. Based on educational level, verbal abuse is more prominent in junior high school/Islamic junior high school students compared to senior high school students, indicating that early adolescence is a more vulnerable phase. Overall, verbal abuse appears in the form of normalized verbal interactions and has the potential to affect students' psychological well-being and social relationships.